Public Sector’s Managerial and Financial Accountability - ISLAMIYAH, YUNITA (The International Journal of Accounting and Business Society, 2017)
Abstract The aims of this study is to explore the financial and managerial accountability of public sector and its institutionalization. The process of institutionalization was comprehended through the perspective of New Institutional Theory (NIT). The Type of this research is qualitative approach using a case study in The Government of Jombang in Indonesia. The New Institutional Theory (NIT) in organizational studies is related to the fact that the structure of an organization is influenced by the social environment where it is located. Organization has a function to maintain its existence through the process of adaptation or institutionalization. Symptoms of isomorphism occurs where the formal organization similar to the environment through the mechanism of coercive, normative and mimetic. On financial accountability, coercive and normative mechanisms seem to be the most dominant. While on managerial accountability, the coercive mechanisms is the most dominant. Decoupling behavior emerges as a response of the organization in addressing changes in financial and managerial accountability. The response shown in the process of institutionalization of financial accountability is acquiescence and compromise strategy. While, managerial accountability tends to use acquiescence and avoidance strategy. Financial accountability has been institutionalized in everyday practice of organization members. Meanwhile, managerial accountability, is a mere formality for compliance with regulations (ceremonial administrative). The results showed that the mechanism of Reward and Punishment (RNP) from the central government supports the process of institutionalization of accountability.